2020
DOI: 10.3390/geriatrics5010019
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Frailty Status with Low-Mileage Driving and Driving Cessation in a Cohort of Older Drivers

Abstract: The US older adult population is projected to considerably increase in the future, and continued driving mobility is important for health aspects in populations with fewer transportation alternatives. This study evaluated whether frailty is associated with low-mileage driving (<1865 miles per year) and driving cessation among older adults. Baseline demographics and health data were collected for 2990 older drivers via in-person assessments and questionnaires, with 2964 reporting baseline frailty data. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…We performed a multiple logistic regression analysis to clarify whether driving cessation was the cause of further physical frailty. As a previous study has reported that baseline frailty status was associated with driving cessation, 30 future research should use designs that can help clarify the causal relationship. However, despite its limitations, this study provided a comprehensive assessment within a large prospective sample of community-dwelling older adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a multiple logistic regression analysis to clarify whether driving cessation was the cause of further physical frailty. As a previous study has reported that baseline frailty status was associated with driving cessation, 30 future research should use designs that can help clarify the causal relationship. However, despite its limitations, this study provided a comprehensive assessment within a large prospective sample of community-dwelling older adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Non-opioids can also impair psychomotor skills relevant to driving. For example, indomethacin and phenylbutazone (but not acetylsalicylic acid) affected eye-hand coordination and divided attention up to 150 min after their administration [194]. Some authors found a significantly increased accident rate after taking non-steroidal antiinflammatory drugs (e.g., [52]).…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…Frailty is a syndrome following a decline in function and resilience across numerous physiological systems [ 195 ]. It is defined as “a clinical state in which there is an increase in an individual’s vulnerability for developing increased dependency and/or mortality when exposed to a stressor” [ 196 ].…”
Section: Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with driving reduction and avoidance include the presence of health conditions, increased frailty, cognitive impairment, concern about crashing, lack of driving comfort, lifestyle changes, and perceptual (especially visual) declines (Crowe et al, 2020;Devlin & McGillivray, 2014;Dickerson et al, 2007;Kandasamy et al, 2018;Molnar et al, 2013;Ragland et al, 2004). The influence of vision problems on driving reduction/avoidance has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%